2022
DOI: 10.1002/ps.7030
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the habitat suitability of the invasive white mango scale,Aulacaspis tubercularis; Newstead, 1906 (Hemiptera: Diaspididae) using bioclimatic variables

Abstract: BACKGROUND: The white mango scale, Aulacaspis tubercularis (Hemiptera: Diaspididae), is an invasive pest that threatens the production of several crops of commercial value including mango. Though it is an important pest, little is known about its biology and ecology. Specifically, information on habitat suitability of A. tubercularis occurrence and potential distribution under climate change is largely unknown. In this study, we used four ecological niche models, namely maximum entropy, random forest, generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…Spatial refinement of the species distribution points was achieved by randomly retaining one distribution point within the overlapping buffer zone 26 . Thus, the minimum ground distance between any two closely spaced distribution points was 5 km 9 . Based on the earlier operations, 117 distribution points were selected, one of which lacked environmental data, resulting in 116 qualified distribution points for modeling, comprising 54 species from 15 genera (Supporting Information Table S1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Spatial refinement of the species distribution points was achieved by randomly retaining one distribution point within the overlapping buffer zone 26 . Thus, the minimum ground distance between any two closely spaced distribution points was 5 km 9 . Based on the earlier operations, 117 distribution points were selected, one of which lacked environmental data, resulting in 116 qualified distribution points for modeling, comprising 54 species from 15 genera (Supporting Information Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…We used the ‘sdmData’ function to generate 1000 ‘pseudo‐absence’ points randomly before combining them with 116 distribution records for modeling. Research has shown that randomly selecting pseudo‐absence data in species distribution modeling can yield the most reliable ENMs 40 and the selection of these 1000 ‘pseudo‐absence’ points was based on recommendations from previous studies 9,19,41,42 . Moreover, the 116 distribution records were sufficient for accurate modeling since accuracy was near maximum when there were 50 data points 19,43 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations